Graphene Nanobeacons with High‐Affinity Pockets for Combined, Selective, and Effective Decontamination and Reagentless Detection of Heavy Metals. Issue 33 (1st July 2022) - Panáček, David; Zdražil, Lukáš; Langer, Michal; Šedajová, Veronika; Baďura, Zdeněk; Zoppellaro, Georgio; Yang, Qiuyue; Nguyen, Emily P.; Álvarez‐Diduk, Ruslan; Hrubý, Vítězslav; Kolařík, Jan; Chalmpes, Nikolaos; et al.
Abstract: Access to clean water for drinking, sanitation, and irrigation is a major sustainable development goal of the United Nations. Thus, technologies for cleaning water and quality‐monitoring must become widely accessible and of low‐cost, while being effective, selective, sustainable, and eco‐friendly. To meet this challenge, hetero‐bifunctional nanographene fluorescent beacons with high‐affinity pockets for heavy metals are developed, offering top‐rated and selective adsorption for cadmium and lead, reaching 870 and 450 mg g ‐1, respectively. The heterobifunctional and multidentate pockets also operate as selective gates for fluorescence signal regulation with sub‐nanomolar sensitivity (0.1 and 0.2 nm for Pb 2+ and Cd 2+, respectively), due to binding affinities as low as those of antigen‐antibody interactions. Importantly, the acid‐proof nanographenes can be fully regenerated and reused. Their broad visible‐light absorption offers an additional mode for water‐quality monitoring based on ultra‐low cost and user‐friendly reagentless paper detection with the naked‐eye at a limit of detection of 1 and 10 ppb for Pb 2+ and Cd 2+ ions, respectively. This work shows that photoactive nanomaterials, densely‐functionalized with strong, yet selective ligands for targeted contaminants, can successfully combine features such as excellent adsorption, reusability, and sensing capabilities, in a way to extend the material's applicability, its life‐cycle, and value‐for‐money. Abstract : Graphene fluorescent nanobeacons, equipped with heterobifunctional and multidentate coordination sites for lead and cadmium, enable selective and highly effective decontamination of natural water, even after recycling and reuse. The high‐affinity pockets on the nanographenes also act as selective sensors for water quality monitoring with sub‐nanomolar sensitivity to lead and cadmium.